Ergenlerin Akran Zorbalığı Yapmaları, Zorbalığa Maruz Kalmaları ve Empatik Eğilimleri Arasındaki İlişkinin İncelenmesi / Examination of the Correlation between Peer Bullying, Exposed to Bullying, and Emphatic Tendencies of Adolescent - Köksal Akyol, Aysel; Bilbay, Asuman (Journal of History Culture and Art Research, 2018)
Abstract The purpose of this study is to examine the correlation between peer victimization, being exposed to victimization, and emphatic tendencies in adolescent and to determine whether or not gender of the adolescent had an effect on peer victimization, being exposed to victimization, and emphatic tendency. The study was conducted via survey method. The sample group of the study consisted of 185 student studying at the seventh and eighth grades of a secondary school, which was affiliated with Sivas Directorate of National Education and randomly determined, during spring term of the school year of 2015-2016. The data were collected by using “Peer Bullying Scale- Adolescent Form” developed by Pişkin and Ayas (2007) in order to determine the students bullying (bully), and being exposed to bullying (victim), and the “Child and Adolescent KA-SI Empathic Tendency Scale” developed by Kaya and Siyez (2009) to determine emphatic tendencies of students. The data were analyzed by using Pearson’s Correlation test for determining the correlation between peer victimization, being exposed to victimization and empathic tendencies in adolescent and t test for determining the effect of gender on peer victimization, being exposed to victimization and empathic tendencies. As a result of these analyses, it was observed that there was no correlation between peer victimization and empathic tendency (p>0.05) and there was a negative correlation between the peer victimization and empathic tendency (p<0.01). It was also revealed that gender of the adolescent had no effect on peer victimization and being exposed to victimization (p>0.05), however, it was found that this led to a difference on empathic tendency in favor of girls (p<0.01). As a result of the study and in accordance with the results, suggestions were offered to the researchers, and members of profession working with children. Öz Bu çalışmanın amacı; ergenlerin akran zorbalığını yapmaları, zorbalığa maruz kalmaları ve empatik eğilimleri arasındaki ilişkinin incelenmesi ile akran zorbalığını yapma, zorbalığa maruz kalma ve empatik eğilim üzerinde ergenlerin cinsiyetinin etki edip etmediğinin belirlenmesidir. Araştırma tarama modelindedir. Araştırmada çalışma grubu 2015-2016 eğitim öğretim yılı bahar döneminde, Sivas Milli Eğitim Müdürlüğü’ne bağlı tesadüfi olarak belirlenen bir ortaokulun yedinci ve sekizinci sınıfa devam eden 185 öğrenciden oluşmuştur. Veriler; zorbalık yapan (zorba) ve zorbalığa uğrayan (kurban) öğrencileri belirlemek için Pişkin ve Ayas’ın 2007’de geliştirdiği “Akran Zorbalığı Belirleme Ölçeği Ergen Formu” ve öğrencilerin empatik eğilimlerini belirlemek için Kaya ve Siyez’in (2009) geliştirdiği “KA-Sİ Çocuk ve Ergenler İçin Empatik Eğilim Ölçeği” kullanılarak toplanmıştır. Verilerin analizinde; ergenlerin akran zorbalığını yapmaları, zorbalığa maruz kalmaları ve empatik eğilimleri arasındaki ilişkinin belirlenmesi için Pearson Korelasyon testi, cinsiyetin akran zorbalığı, zorbalığa maruz kalma ve empatik eğilim üzerindeki etkisini belirlemek için t testi kullanılmıştır. Yapılan bu analizler sonucunda; zorbalığa maruz kalmayla empatik eğilim arasında herhangi bir ilişkinin olmadığı (p>0,05), akran zorbalığı yapmayla empatik eğilim arasında negatif yönde bir ilişkinin olduğu (p<0,01) görülmüştür. Ergenlerin cinsiyetlerinin akran zorbalığını yapma ve zorbalığa maruz kalma üzerinde herhangi bir etkisinin olmadığı (p>0,05), ancak empatik eğilim üzerinde kızlar lehine bir farklılığa neden olduğu (p<0,01) belirlenmiştir. Araştırmanın sonucunda, elde edilen bulgular ışığında araştırmacı ve çocuklarla çalışan meslek elemanlarına önerilerde bulunulmuştur.